EFL Learners’ Perception of Class Point Tool Application in Enhancing their Satisfaction and Active Learning in Classroom (Journal of Contemporary Educational Policies and Practices, 2023)
Attaching the Classroom Response System (CRS) to the teaching process has been a flowering trend recently thanks to its appeal to students’ satisfaction and active learning. This paper set out simply to determine the learners’ perception of the Class Point tool – a modern CRS that was launched in 2015 and has not yet been familiar to Vietnamese educators. After nine times applying the Class Point tool directly in the classrooms, the teachers, also the researchers, conducted an online survey and a semi-structured interview with over two hundred learners from four different EFL English classes at a private institution in Ho Chi Minh City. Far from the expectation, the result of this study proved that participants not only experienced pleasure with the tool but also felt effectively engaged in interactive activities. Furthermore, its modernized features seem to maximize the dominance and minimize the hardship that other CRSs still entail. The finding of this study will enable teachers to further apply the tool in their classroom with a certain view of its benefits.
Keywords: Classroom response system (CRS); active learning (AL); Class Point; students’ satisfaction